Coalescence growth mechanism of inserted tin dioxide belts in polycrystalline SnO2-based ceramics - Masteghin, Mateus G. [UNESP] (2018)
SnO2-based varistors have been considered promising technological devices. However their practical application is usually stated as limited to high voltage circuits based on the high breakdown electric field exhibited by these ceramics. Recently, authors have shown that the insertion of one-dimensional (1D) SnO2 belts allows overcoming this limitation. In this work, we present a detailed study of the growth mechanism of the belts inside varistors using electron microscopy techniques. We were able to show that mass transport has an intrinsic dependence on the sintering time and requires similar crystalline structure between the belts and the matrix. Dual beam and high-resolution transmission electron microscopy techniques permitted determining that 3D growth of belts occurs by coalescence.